Risk Factors of Rapid Correction of Severe Hyponatremia in Bhumibol Adulyadej Hospital - Boonyacharaskul, suwit; Pattamin, Nuttapol (Royal Thai Air Force Medical Gazette, 2024)
Background: Severe hyponatremia is a common electrolyte imbalance which can make patients develop neurological symptoms such as headache, nausea, vomiting, and coma. Treatment of severe hyponatremia need to be cautious because overcorrection may lead to serious neurological complications including osmotic demyelination syndrome (ODS). Nowadays, there are limited data on incidence and risk factors of overcorrection of severe hyponatremia. Method: In a retrospective study of 400 patients aged 18 years and older who were hospitalized with serum sodium <120 mEq/L at Bhumibol Adulyadej Hospital from 2018 to 2021, we examined the incidence and risk factors of overcorrection. Overcorrection was defined as a serum sodium increase of ≥10 mEq/L at 24 hours and ≥18 mEq/L at 48 hours. Data on patient’s characteristics were collected and analyzed using descriptive and analytical statistics. Result: Of all 400 patients with severe hyponatremia, 84 patients (21%) experienced overcorrection. Multivariate analysis revealed that the risk factors for overcorrection of severe hyponatremia include age younger than 65 years (odd ratio (OR) 1.99, 95% Confidence Interval (CI) 1.2-3.31, P-value 0.008), initial serum sodium lower than 115 mEq/L (OR 2.10, 95%CI 126-3.48, P-value 0.004) and hypovolemic volume status (OR 2.60, 95%CI 1.55-4.35, P-value <0.001). ODS following overcorrection was found in 4 patients accounted as 1% of population. Conclusion: Among patients hospitalized with severe hyponatremia, overcorrection was occurred in 21%. The risk factors for overcorrection are age younger than 65 years, initial serum sodium lower than 115 mEq/L and hypovolemic volume status.